Capitalism in the web of life : ecology and the accumulation of c apital - Moore, Jason W. (New York : Verso, 2015)
"Both green and red analyses of capitalism's deepening contradiction s have acknowledged the close relation of economic and environmental cr ises. But environmentalists have not yet fully integrated social and hi storical factors in their scathing indictment of the current disaster. Capitalism in the Web of Life will undoubtedly help to change that. Ch arting the recurrent crises, and long cyclical expansions of capitalism as socio-ecological process over the past six centuries, Jason Moore p rovides a groundbreaking theory and historical account of capitalism's development that comprehends the transformation of nature as constituti ve of capital accumulation. Along the way, he moves beyond the society/ nature distinction that limits so much environmentalism"--
"Both green and red analyses of capitalism's deepening contradiction s have acknowledged the close relation of economic and environmental cr ises. But environmentalists have not yet fully integrated social and hi storical factors in their scathing indictment of the current disaster. Capitalism in the Web of Life will undoubtedly help to change that. Cha rting the recurrent crises, and long cyclical expansions of capitalism as socio-ecological process over the past six centuries, Jason Moore pr ovides a groundbreaking theory and historical account of capitalism's d evelopment that comprehends the transformation of nature as constitutiv e of capital accumulation. Along the way, he moves beyond the society/n ature distinction that limits so much environmentalism"--
Includes bibliographical references and index.
Keywords: Economic development -- Environmental aspects; Economic policy -- Environmental aspects; Environmental policy